A new genus and species of cave-dwelling terrestrial isopod (Crustacea: Oniscidea: Trichoniscidae) from Southern Spain - Garcia, Lluc; Miralles-Núñez, Adrià; Pérez-Fernández, Toni (Zootaxa, 2020)
A new genus of terrestrial isopod (Oniscidea) belonging to the family Trichoniscidae, subfamily Haplophthalminae, Baeticoniscus n. gen., is described. We discuss its affinities and differences with the other genera of the same subfamily, which are characterized by presenting a completely smooth third pleonite. Baeticoniscus bullonorum n. sp. is described and designated as a type species of the new genus. The specimens of this new isopod come from the Cueva de la Pileta of Benaoján in the province of Málaga (Andalusia, Spain).